Nanostructured Materials: Bioengineering Platforms for Sensing Nucleic Acids - Md. Eaqub, Ali; Md.M., Rahman; Th. S., Dhahi; Muhammad, Kashif; Md. Shaheen, Sarkar; Wan Jeffrey, Basirun; Hamid, SBA; Bhargava, Suresh (Elsevier, 2016)
Detection of specific nucleic acid targets is of enormous and increasing interest in molecular biodiagnostics, food analysis, forensic investigation, and environmental monitoring. The advancement of nanotechnology with a myriad of novel and engineered nanomaterials and their hybrids with attractive physiochemical properties has raised hopes for the development of DNA sensors capable of identifying specific nucleic acid sequences with single molecule precision, avoiding the need of skilled personnel or sophisticated machineries. Compared to the traditional sensing platforms, DNA–nanomaterial hybrids provide better sensitivity and multiplexing facility, reducing analysis cost and increasing detection precision by several orders of magnitudes. The biofusion of DNA with nanostructured gold, nanostructured silica, nanogap semiconductors, carbon nanotubes, graphenes, and quantum dots has shown great possibilities to fabricate specialized nanostructured configurations capable of enhancing DNA detection several-fold. Miniaturized devices with embedded DNA of thousands of fingerprints in lab-on-a-chip are no longer a surprise. Here, we describe potential candidate nanomaterials and their molecular binding patterns with DNA to constitute a sensing platform for nucleic acid targets. The future perspectives and challenges of nanotechnology strategies are also outlined